PENELITIAN DEPOSISI ASAM DI SITU PATENGAN PROPINSI JAWA BARAT - Simon S Brahmana (Bina Teknik Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2009)
In order to find out the level of acid deposition especially in West Java's inland water aquatic, and inline with the active participation of the Research Center for Water Resources in the Network for AcidDeposition Monitoring in East Asia, a study was conducted on the degree of inland water aquatic acidity inLake Patengan from 1999 to 2007. This study was based on descriptive method, observations, includingthe collection of secondary data and field sampling and sample analysis in the laboratory of theExperimental Station for Water Resources Environment according to the 1996 compendium of IndonesianNational Standard (SNI), SNI 2004 and the Acid Deposition Monitoring Network in East Asia (EANET)2001. Results of study show that from 1999 until 2007, average pH value of each year had increased from 7.7to 8.3, but from 2002 up to 2007, average pH of water in Lake Patengan had decreased each year from 8.3 to7.8. In general, the ion balance is still good. From 1999 to 2007, pH in Patengan lake increased from 7.1to 8.4 with average 7.8 and standard deviation 0.3865. However, acid deposition was not identified by theinland water aquatic conditions at Situ Patengan, West Java , Indonesia.